From Forbidden to Cure-All - Hallonsten, Olof (Empty Innovation: Causes and Consequences of Society's Obsession with Entrepreneurship and Growth, 2023)
Innovation was not always viewed positively in society and the economy. In fact, there is evidence that for the better part of human history it was viewed as a threat, and generally forbidden. Only in the past century has innovation risen to prominence, first as a concept and explanatory model in economics, and later as a cure-all in economic policymaking, in the wake of economic crises and the growing global competitiveness between nations, regions, and industries. This chapter accounts for the transformation of the concept of innovation from forbidden to cure-all, including a historicization and conceptualization of the basics of innovation policy.